2023
DOI: 10.7759/cureus.38395
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi’s Varicelliform Eruption After Treatment With Ixekizumab in a Patient With Pityriasis Rubra Pilaris

Abstract: Pityriasis rubra pilaris (PRP) is a rare condition characterized by red-orange plaques with islands of sparing with follicular and palmoplantar hyperkeratosis. The disease can be difficult to treat and often requires patients to trial multiple therapeutic options. In recent years, targeted biologic therapies have increasingly been trialed due to their relative efficacy and favorable safety profile. Ixekizumab, an interleukin-17 inhibitor, is one such therapy that has demonstrated efficacy in PRP with few repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…KVE is a cutaneous viral infection, which is mainly caused by herpes simplex virus and presents as widespread clustered vesicles that evolve into punched-out erosions [ 14 ]. While KVE has been predominantly associated with atopic dermatitis, it can also occur in other skin conditions such as PRP, acantholytic dermatosis, burns, mycosis fungoides and others [ 14 , 15 ]. To our knowledge, to this date there are only 4 case reports of PRP with KVE described in the literature ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KVE is a cutaneous viral infection, which is mainly caused by herpes simplex virus and presents as widespread clustered vesicles that evolve into punched-out erosions [ 14 ]. While KVE has been predominantly associated with atopic dermatitis, it can also occur in other skin conditions such as PRP, acantholytic dermatosis, burns, mycosis fungoides and others [ 14 , 15 ]. To our knowledge, to this date there are only 4 case reports of PRP with KVE described in the literature ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Erdag et al, suggested that KVE in case of PRP could be exacerbated by local corticosteroids and UVB phototherapy [ 16 ], while Cavalie et al, provided evidence supporting the potential role of phototherapy in development of KVE [ 15 ]. Guenther et al presented an intriguing case of PRP with KVE and Pseudomonas aeruginosa superinfection, where development of KVE was associated with IL-17A inhibitor use, recent COVID-19 infection, and compromised skin barrier integrity [ 14 ]. In our case, the use of immunosuppressive treatment with methotrexate, recent COVID-19 infection and severely damaged skin barrier may have contributed impact to the development of KVE.…”
Section: Discussionmentioning
confidence: 99%